Exploring Students’ Perception of Speech Practice in Academic Speaking Subject for Fifth-Year Students - Ila Wulan Windari; Farid Noor Romadlon; Rusiana (LPPM Universitas PGRI Semarang, 2026)
In the era of globalization, public speaking is becoming increasingly important in various fields, especially for EED students as future educators, where they must present material and lead class discussions effectively. However, many struggle to develop it, such as with anxiety and a lack of confidence. This research aims to describe the perceptions of EED students at Muria Kudus University regarding speech practice in the Academic Speaking subject during the 2024/2025 academic year, in terms of the activities, benefits, and challenges. This research uses a qualitative method with a phenomenological approach. Data were collected from 10 fifth-semester students of the English Education Department (EED) at Muria Kudus University through open-ended questionnaires and analysis of the academic speaking syllabus (RPS) regarding speaking activities, learning outcomes, and teaching methods. Thematic analysis was used to examine the data, and credibility was ensured through data triangulation by comparing questionnaire results with the syllabus content. The findings indicate that overall, students have positive perceptions, highlighting increased confidence, fluency, and organization of their ideas, after participating in speech practice using repetition strategies. Additionally, five aspects of verbal behavior were found to align with Skinner's theory, while two aspects did not. However, there are challenges such as nervousness, limited vocabulary, and fear of making mistakes, but this does not hinder the improvement of skills.